2016
DOI: 10.1007/s11010-016-2730-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepcidin and its downstream proteins in early brain injury after experimental subarachnoid hemorrhage in rats

Abstract: Early brain injury (EBI) is a major cause of mortality from subarachnoid hemorrhage (SAH). We aimed to study the pathophysiology of EBI and explore the role of hepcidin, a protein involved in iron homeostatic regulation, and its downstream proteins. One hundred and thirty-two male Sprague-Dawley rats were assigned into groups (n = 24/group): sham, SAH, SAH + hepcidin, SAH + hepcidin-targeting small interfering ribonucleic acid (siRNA), and SAH + scramble siRNA. Three hepcidin-targeting siRNAs and one scramble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…In physiological conditions hepcidin expression in brain structures and cells (neurons, glial cells, endothelial cells, epithelial cells of choroid plexus) has been consistently observed by in vivo studies in humans and rodents, albeit in low levels ( Krause et al, 2000 ; Pigeon et al, 2001 ; Zechel et al, 2006 ; Wang et al, 2008 , 2010 ; Hänninen et al, 2009 ; Raha et al, 2013 ; Wei et al, 2014 ; Farajdokht et al, 2015 ; Raha-Chowdhury et al, 2015 ; Graf et al, 2016 ; Li Y. et al, 2016 ; Pan et al, 2016 ; Tan et al, 2016 ; Lu et al, 2017 ; You et al, 2017 ; Zhang et al, 2017 ). Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ). Similar to other cells, hepcidin main target protein in brain cells is FPN, but also iron import proteins ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 83%
See 2 more Smart Citations
“…In physiological conditions hepcidin expression in brain structures and cells (neurons, glial cells, endothelial cells, epithelial cells of choroid plexus) has been consistently observed by in vivo studies in humans and rodents, albeit in low levels ( Krause et al, 2000 ; Pigeon et al, 2001 ; Zechel et al, 2006 ; Wang et al, 2008 , 2010 ; Hänninen et al, 2009 ; Raha et al, 2013 ; Wei et al, 2014 ; Farajdokht et al, 2015 ; Raha-Chowdhury et al, 2015 ; Graf et al, 2016 ; Li Y. et al, 2016 ; Pan et al, 2016 ; Tan et al, 2016 ; Lu et al, 2017 ; You et al, 2017 ; Zhang et al, 2017 ). Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ). Similar to other cells, hepcidin main target protein in brain cells is FPN, but also iron import proteins ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 83%
“…During brain hemorrhage/ischemia liver hepcidin is upregulated, which is accompanied with increased global brain iron content after peak levels of hepcidin ( Xiong et al, 2016 ). Importantly, hepcidin knockout decreases brain iron content in models with brain hemorrhage, but not in physiological conditions ( Tan et al, 2016 ; Xiong et al, 2016 ). Xiong et al (2016) study found a significantly lower brain iron content in hepcidin knockout rodents compared to normal rodents during intracerebral hemorrhage (ICH).…”
Section: Role Of Systemic Hepcidin In Brain Homeostasismentioning
confidence: 97%
See 1 more Smart Citation
“…28 Therefore, it can cause iron accumulation within the cell when overexpressed 29. Hepcidin expression is increased in response to cellular iron overload and inflammation 30.…”
Section: Iron Homeostasis In Normal Brainmentioning
confidence: 99%
“…A pilot study in human patients suggested a causal relationship between free iron in the CSF following SAH and brain injury 150. Indeed, suppression of hepcidin (and thus inhibition of FP1 internalisation) attenuated brain damage following experimental SAH, suggesting the importance of intracellular iron accumulation 29. This suggests that the initial inflammation caused by iron accumulation stimulates hepcidin expression, which in turn leads to a decreased efflux of iron from these cells.…”
Section: Subarachnoid Haemorrhagementioning
confidence: 99%